UTILIZATION OF INTERNET AS AN ALTERNATIVE MEDIA TO LEARN ENGLISH INDEPENDENTLY OUTSIDE CLASSROOM - Witri Handayani; Hendro Saptopramono (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Nowadays, lnternet has brought essential influence to human life. People may consider it as one of their primary needs. Internet has been easily accessed because many public places provide WI-FI  facility so everyone can stay connected with internet. In order to accommodate this necessity, State Polytechnic of Padang also provides free access of intemet in the campus. Actually, this internet facility should give beneficial aspects to students especially in improving their ability and understanding in English. There are many websites or blogs that offer great oppoftunity for students to improve their competence in mastering English skills. However. students sometimes cannot use this opportunity maximally. There are two reasonable factors why students cannot gain optimal benefit of internet utilization. Firstly, they do not know certain links of websites that provide English learning materials which are useful for them. Secondly, they do not have sufficient knowledge to utilize the content from essential websites or blogs for improving their English competence. The article then focuses on introducing useful links available in internet based on category which are demanded by students such as listening, speaking, writing, reading, grammar and English tests. Furthermore, this article also explores required knowledge and skills that must be acquired by students to gain benefit in utilizing contents from websites or blog as media of English learning outside of their classroom. By gaining these knowledge and skills students will be able to develop their independent language learning.